Xenophyophores (Rhizaria, Foraminifera) from the Nazaré Canyon (Portuguese margin, NE Atlantic) - Gooday, A.J.
Xenophyophores are abundant on a terrace of the lower Nazaré Canyon (4300 m water depth) on the Portuguese margin. Here, the most abundant species, Reticulammina cerebreformis sp. nov., occurs in densities of up to 21 individuals/m2. This large species has a soft, friable hemispherical test up to 10 cm in diameter consisting of curved, sinuous plates (lamellae) that branch and anastomose. The plates are separated by deep furrows and other depressions to form a distinctive ‘brain-like’ structure. The outer test layer is thin, weakly cemented and is dominated by fine sediment particles; the internal xenophyae include a higher proportion of larger mineral grains. The second new species at the 4300-m site, Nazareammina tenera gen. et sp. nov., is much less common. The test is basically plate-like, but towards the interior it is perforated by oval spaces, which typically merge into complex system of bar-like features, sometimes with irregular excrescences. The granellare system (cell body and its organic envelope) is packed with tiny mineral grains of various sizes and shapes, including titanium-bearing particles. Also common at this deep site are clusters, with a maximum diameter up to 10 cm or occasionally more, of irregular tubes belonging to Aschemonella ramuliformis Brady 1884, a species previously known mainly from isolated tubes. Rather than being single individuals, these clusters comprise a large number of separate branched tubes. Finally, Syringammina fragillissima Brady 1883, a well-known species that is widely distributed on the NW European margin, occurred on steep sediment-covered slopes at a shallower (1555 m water depth) site in the upper canyon. Almost complete SSU rDNA gene sequences obtained from A. ramuliformis and R. cerebreformis confirm that these xenophyophores are foraminifera. Together with two previously sequenced xenophophores (Shinkaia lindsayi Lecroq, Gooday, Tsuchiya, Pawlowski 2009 and Syringammina corbicula Richardson 2001), and the foraminiferan Rhizammina algaeformis, they constitute a clade within the radiation of monothalamous foraminifera. In situ photographs of R. cerebreformis and A. ramuliformis reveal no evidence of pseudopodia deployed onto the sediment surface. Instead, these species probably trap sediment within their complex, folded test surface (R. cerebreformis) or intercept suspended particles (A. ramuliformis).